From I to ethos: the multifaceted Lucio V. Mansilla regarding the Ranquele’s speech - Zaslavsky, Danielle (Boletín de Filología, 2020)
This article examines the representations of the Araucanian world in Lucio V. Mansilla’s Una excursión a los indios ranqueles, a travel story published in Buenos Aires in 1870. Drawing on a discursive and argumentative approach, the article analyses and explores how, via the different ethos set out in the story, e.g. that of the ethnographer, the philologist, the politician, the soldier and the literary man; as well as through his description of the indigenous world, Mansilla tries to denounce the dichotomy barbarism-civilization. Based on his own experience with the Ranquele Indians, Mansilla establishes a series of analogies between the discursive interactions of the Ranqueles and the political modalities of the “civilized” world, that reveals a subtle understanding of all the language dimensions. In his description, which could be that of a contemporary discourse analyst, the Ranqueles are portrayed as being on par with any Argentinean politician. However, Mansilla’s discursive universe, which is that of a cultured and literate politician of his time, and the mixed audience he targets, result in a rather heterogeneous vision of the indigenous world whose impending extermination he is trying to prevent.